2022
DOI: 10.1002/1878-0261.13282
|View full text |Cite
|
Sign up to set email alerts
|

Profiling the 3D interaction between germ cell tumors and microenvironmental cells at the transcriptome and secretome level

Abstract: The tumor microenvironment (TM), consisting of the extracellular matrix (ECM), fibroblasts, endothelial cells, and immune cells, might affect tumor invasiveness and the outcome of standard chemotherapy. This study investigated the cross talk between germ cell tumors (GCT) and surrounding TM cells (macrophages, T‐lymphocytes, endothelial cells, and fibroblasts) at the transcriptome and secretome level. Using high‐throughput approaches of three‐dimensional (3D) co‐cultured cellular aggregates, this study offers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 84 publications
0
5
0
Order By: Relevance
“…Together with our previous observations of certain molecular analogies between YST and HCC, we identified novel therapeutic targets whose inhibition resulted in apoptosis induction and / or cell cycle arrest in a drug-dependent manner in YST cells, while fibroblasts remained mostly unaffected, thereby opening a therapeutic window for the treatment of (cisplatin-resistant) YST patients. Overall, several phase 2 studies showed only limited clinical benefit from treatment with either the PARP1 / 2 inhibitor Olaparib (Giorgi et al 2020 ) and Veliparib (Mego et al 2021 ), c-Met inhibitor Tivantinib (Feldman et al 2013 ), ABL1 / 2 / KIT / PDGFRA / B inhibitor Imatinib (Einhorn et al 2006 ; Piulats et al 2007 ), BRAF / FGFR1 / KIT / PDGFRB / RAF1 inhibitor Sorafenib (Skoneczna et al 2014 ), VEGFR1-3 / PDGFR / FGFR / KIT / c-Fms inhibitor Pazopanib (Necchi et al 2017 ), mTOR inhibitor Everolimus (Fenner et al 2018 ), or VEGFR2 / PDGFRB inhibitor Sunitinib (Feldman et al 2010 ; Oechsle et al 2011 ; Reckova et al 2012 ) in heavily pretreated refractory GCT patients. Nevertheless, most of these studies did not stratify between GCT subtypes, so that no conclusion can be taken with regard to the efficacy for YST patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Together with our previous observations of certain molecular analogies between YST and HCC, we identified novel therapeutic targets whose inhibition resulted in apoptosis induction and / or cell cycle arrest in a drug-dependent manner in YST cells, while fibroblasts remained mostly unaffected, thereby opening a therapeutic window for the treatment of (cisplatin-resistant) YST patients. Overall, several phase 2 studies showed only limited clinical benefit from treatment with either the PARP1 / 2 inhibitor Olaparib (Giorgi et al 2020 ) and Veliparib (Mego et al 2021 ), c-Met inhibitor Tivantinib (Feldman et al 2013 ), ABL1 / 2 / KIT / PDGFRA / B inhibitor Imatinib (Einhorn et al 2006 ; Piulats et al 2007 ), BRAF / FGFR1 / KIT / PDGFRB / RAF1 inhibitor Sorafenib (Skoneczna et al 2014 ), VEGFR1-3 / PDGFR / FGFR / KIT / c-Fms inhibitor Pazopanib (Necchi et al 2017 ), mTOR inhibitor Everolimus (Fenner et al 2018 ), or VEGFR2 / PDGFRB inhibitor Sunitinib (Feldman et al 2010 ; Oechsle et al 2011 ; Reckova et al 2012 ) in heavily pretreated refractory GCT patients. Nevertheless, most of these studies did not stratify between GCT subtypes, so that no conclusion can be taken with regard to the efficacy for YST patients.…”
Section: Discussionmentioning
confidence: 99%
“…The used (tumor) cell lines were cultured as described previously and summarized in Additional file 5 : Table S1A (Skowron et al 2021b ; Burmeister et al 2022 ). Polarization of THP-1 cells was described earlier and was based on Genin et al ( 2015 ), Skowron et al ( 2022 ). XTT cell viability assays upon treatment with inhibitors (Additional file 5 : Table S1B) were performed as described previously (Skowron et al 2022 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Establishment of CD24-deficient EC cell lines (DCD24) via CRISPR/Cas9 technology was performed as reported previously [4,17,18]. For 3D cultivation in hanging drops, similar to our previous studies [19,20], 3 9 10 3 tumour cells per drop (40 lL) were seeded onto an inverted lid of a 15-cm cell culture dish before being inverted back onto the bottom chamber filled with phosphate-buffered saline for humidity. The next day, NK-92 or NK-92-CD24-CAR cells were added in the same manner at a ratio of 1 : 3 (9 x 10 3 ) in a volume of 10 lL per drop, supplemented with recombinant human interleukin-2 (Peprotech via Biozol, Eching, Germany), with a final concentration per drop of 5 ngÁmL À1 .…”
Section: Cell Culturementioning
confidence: 99%
“…Other soluble factors, in particular IL-8, can lead to an increase in NF-kB and ABCB1, which are responsible of reduced Cisplatin sensitivity: this mechanism, described in gastric cancer cells, could be applicable to GCTs as well ( 71 ). It is therefore interesting to note that precisely the destruction of tumor cells mediated by platinum-based chemotherapy could at the same time stimulate the secretion of protumoral factors in the tumor stroma ( 72 ).…”
Section: Immune-related Biomarkers In Gctsmentioning
confidence: 99%